Analisis Faktor-faktor Penyebab Kecurangan Laporan Keuangan Berdasarkan Teori Fraud Hexagon - Handoko, Excellino Gegana; Mardjono, Enny Susilowati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of financial reports is to provide information related to the company's finances. This study aims to determine the effect of Fraud Hexagon (Pressure, Opportunity, Justification, Ability, Arrogance, Collusion) on the condition of financial reports. The sample of this study was conducted using purposive sampling, which has the criteria of BUMN companies on the BUMN.go.id website in the form of PT (Limited Liability Company) companies that publish annual reports from 2021 to 2024. Data in the form of secondary data taken from IDX and/or the official website of the entity as many as 117 samples. The analysis tool used is WarpPLS 7.0 to determine the effect of Fraud Hexagon on financial reports so that companies can identify and anticipate fraud that occurs in the field. The results show that the variables that affect the condition of financial reports are pressure (X1) which is proxied by financial targets, opportunities (X2) which is proxied by commissioner communication, and ability (X4) which is proxied by director changes. Justification (X3) which is proxied by auditor changes, arrogance (X5) which is proxied by the CEO holding dual positions, and collusion (X6) which is proxied by audit fees, do not affect financial reporting events.